RADICAL PROSTATECTOMY WITH EXTENDED PELVIC LYMPHADENECTOMY AND ADJUVANT HORMONAL THERAPY IN PATIENTS WITH LYMPHOGENIC DISSEMINATED PROSTATE CANCER - B. Ya. Alekseev (Onkourologiâ, 2014)
The main radical treatments for patients with prostate cancer (PC) are radical prostatectomy (RPE) and radiotherapy. At the same time pelvic lymphadenectomy (PLAE) in patients with PC is an important diagnostic step during both surgical and radiation treatments. The main goal of PLAE is to evaluate the pelvic lymph nodes. The paper gives the data of a number of trials of the efficiency of RPE with extended PLAE and adjuvant hormonal therapy.